Paravani, a puzzling lake in the South Caucasus. (30th March 2021) - Messager, Erwan; Poulenard, Jérôme; Sabatier, Pierre; Develle, Anne-Lise; Wilhelm, Bruno; Nomade, Sébastien; Scao, Vincent; Giguet-Covex, Charline; Von Grafenstein, Ulrich; Arnaud, Fabien; Malet, Emmanuel; Mgeladze, Ana; et al.
Abstract: Sediments of Lake Paravani, the largest natural lake in the South Caucasus, were analysed to reconstruct the millennial history of the environment. Pollen analysis, previously undertaken on the first core retrieved in the middle of the lake, revealed a vegetation history for the last 12 millennia. As part of the present study, a new core was taken from the north-western part of the lake. Pollen analysis was performed on this new core with the same methodology as for the previous one. A sedimentological and geochemical analysis was also conducted on both cores in order to gain an understanding of the dynamics of erosion in the catchment area in response to landscape modifications. The results show that the sediment deposits within Lake Paravani yield rather complex and puzzle-like palaeoecological records. Despite the differences between the two records, correlations have been made that are supported by the 14C dates. By combining all of the data from both cores, it was finally possible to reconstruct the puzzle of the environmental history recounted by the Lake Paravani sediments. This reconstructed history is composed of four main phases: 1. A steppic environment marked by pronounced erosion processes from 12 000 to 10 000 cal. BP; 2. A transition phase characterized by the expansion of grasses (Poaceae) from 10 000 to 9-8 000 cal. BP; 3. A more forested phase from 9-8 000 to 2 000 cal. BP, during which the erosion fluxes decreased; and 4. A decline in tree cover probably due to human activities over the last 2 millennia.